2009
DOI: 10.1007/s11706-009-0038-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of powder particle size on green properties and stress wave

Abstract: In the powder metallurgy (PM) industry, high velocity compaction (HVC) technique is a new way to obtain higher density parts. In this study, three reduced pure iron powders with different particle sizes were pressed by HYP35-2 High Velocity Compaction Machine. A computer controlled universal testing machine was used to measure the bending strength of the green body. The relationships among the particle size, the impact velocity, the green density, the stress wave, the bending strength and the radial springback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Unbalanced force shows this trend and promotes the evolution of porosity. This phenomenon may be the internal characterization of stress wave [10][11][12], and the relation will be studied in the future.…”
Section: Characterization Of Packing Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Unbalanced force shows this trend and promotes the evolution of porosity. This phenomenon may be the internal characterization of stress wave [10][11][12], and the relation will be studied in the future.…”
Section: Characterization Of Packing Structurementioning
confidence: 99%
“…In addition, the peaks of stress wave increase with increasing impact height, and high density can be related to high impact height. Wang et al [11] also found that the HVC of iron powder of different sizes may have similar pulsed waveforms. The duration of the first peak decreases gradually, and the density of the powder increases with increasing impact height.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation